Ocular fungal infections - Ramírez Soto, Max Carlos (2022)
[extracted from abstract] Fungal infections of the eye continue to be an important cause of ocular morbidity and loss of vision, particularly in the developing world [1]. These infections have increased in recent decades due to broad-spectrum antibiotic use, the growing number of patients undergoing procedures that lead to immunosuppression, postoperative infection, trauma, and prolonged corticosteroid use [2]. Ocular fungal infections are categorized by the anatomical location of the infection. These infections can occur around the eye (ocular adnexa), or in the eye, including the anterior and posterior segments of the eye [3]. Major pathogenic fungi of the eye include Aspergillus, Candida spp., Cryptococcus species, and Coccidioides spp., Fusarium, Penicillium, Pseudallescheria, dimorphic fungi as Histoplasma capsulatum, Blastomyces dermatitidis, Sporothrix spp., and Coccidioides spp. (C.immitis and C. posadasii) [3,4]. The diagnosis of ocular fungal infections can be difficult because of non-specific clinical manifestations. However, in recent years it has been improved by laboratory and diagnostic techniques, and the recognition of the clinical signs of ocular fungal infections [4]. This has increased the frequency of correct diagnosis and prevalence of these diseases. Because of this, it is important to maintain to knowledge of new developments in the diagnosis and management of infectious diseases of the eye. In this setting, in this Special Issue, articles have been published describing novel findings and reviews on the epidemiology, diagnosis, and treatment of ocular fungal infections, with a special focus on infections in ocular adnexa, endophthalmitis, keratitis, and ocular sporotrichosis.